The preventive and therapeutic effect of repetitive transcranial magnetic stimulation on radiation-induced brain injury in mice. (3rd August 2022) - Liu, Li-Yuan; Qin, Tong-Zhou; Guo, Ling; Rong-Rong, Huang; Jing, Yun-Tao; Lai, Pan-Pan; Xue, Yi-zhe; Ding, Gui-Rong
Abstract: Purpose: To clarify the preventive and therapeutic effects of repetitive transcranial magnetic stimulation (rTMS) on brain injury induced by X-ray cranial irradiation, preliminarily identify the mechanism and provide a novel clinical approach for the prevention and treatment of radiation-induced brain injury (RBI). Materials and methods: Male C57BL/6 mice were randomly divided into the sham group, large fractionated dose (5 Gy × 4 d) group, large fractionated dose + rTMS (5 Gy × 4 d + rTMS) group, conventional fractionated dose (2 Gy × 10 d) group and conventional fractionated dose + rTMS (2 Gy × 10 d + rTMS) group. After cranial irradiation and rTMS, behavioral experiments, morphological staining and molecular biology experiments were performed. We further determined the mechanism of rTMS on the prevention and treatment of RBI, including changes in hippocampal neuronal apoptosis, neural stem cell (NSC) proliferation and differentiation, and neuronal synaptic plasticity. Results: rTMS alleviated the negative effects of cranial radiation on the general health of mice and promoted their recovery. rTMS ameliorated the impairment of spatial learning and memory induced by cranial radiation, and this beneficial effect was more robust in the conventional fractionated dose group than the large fractionated dose group. Moreover, rTMS alleviated the alterations in hippocampal structure and neuronal death and had preventive and therapeutic effects against RBI. In addition, rTMS reduced hippocampal cell apoptosis, promoted NSC proliferation and differentiation in the hippocampus after cranial irradiation, and enhanced neuronal synaptic plasticity in the hippocampus. Subsequent studies showed that rTMS upregulated the expression of learning- and memory-related proteins. Conclusion: rTMS could alleviate learning and memory impairment caused by RBI, and the preventive and therapeutic effects of rTMS were better for the conventional fraction radiation paradigms.